Background of Finland's Choice for NATO Membership (Historical Aspect) - A. M. Muller; S. N. Pogodin (Управленческое консультирование)
Discussions about Finland's accession to NATO began in the late twentieth century. The greatest activity on the issue of Finland's membership in the Alliance was the country's accession to the European Union. Finland has stepped up cooperation with NATO in various forms, ranging from arms purchases to participation in peacekeeping  operations. At present, Finland is trying to find new ways to ensure its own security.